Testosterone levels in men with chronic migraine - Lisa B.E. Shields; Tad Seifert; Brent J. Shelton; Brian Plato (MDPI AG, 2019)
Chronic migraine is a frequent and debilitating condition affecting 14% of the general population. This prospective observational pilot study investigated whether men with chronic migraine have lower than expected total serum testosterone levels. We identified 14 men ages 26-51 at our Institution who fulfilled the ICHD-3b criteria for chronic migraine and obtained serum total testosterone levels. The mean total testosterone level in our 14 patients was 322 ng/dL (range: 120-542 ng/dL) which is in the lower 5% of the reference range for our laboratory (300-1080 ng/dL). Men with chronic migraine had lower total testosterone levels compared to published agematched normative median values by a median difference of 62 ng/dL (P=0.0494). This finding suggests that hypothalamic regulation is altered in patients with chronic migraine. Further studies are warranted to determine whether testosterone supplementation in men with chronic migraine reduces the number of headaches or the associated symptoms of hypogonadism.